2011
DOI: 10.1149/1.3581109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ionic Conductivity of the Electrolyte in Composite SOFC Cathodes

Abstract: Solid oxide fuel cell (SOFC) cathodes were prepared by infiltration of 35 wt % La0.8Sr0.2FeO3 (LSF) into porous scaffolds of three, zirconia-based electrolytes in order to determine the effect of the ionic conductivity of the electrolyte material on cathode impedances. The electrolyte scaffolds were 10 mol % Sc2O3-stabilized zirconia (ScSZ), 8 mol % Y2O3-stabilized zirconia (YSZ), and 3 mol % Y2O3- 20 mol % Al2O3-doped zirconia (YAZ), prepared by tape casting with graphite pore formers. Each electrolyte scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 61 publications
3
44
0
Order By: Relevance
“…4,[7][8][9]27,28,[31][32][33][34] The changes in microstructure are demonstrated by the SEM micrographs of LSF-YSZ composites after calcination to 1123 K and 1373 K, presented in Figure 3. For the 1123 K sample, the LSF particles are small, with a characteristic size of about 50 nm, and appear to coat the YSZ channels uniformly.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…4,[7][8][9]27,28,[31][32][33][34] The changes in microstructure are demonstrated by the SEM micrographs of LSF-YSZ composites after calcination to 1123 K and 1373 K, presented in Figure 3. For the 1123 K sample, the LSF particles are small, with a characteristic size of about 50 nm, and appear to coat the YSZ channels uniformly.…”
Section: Resultsmentioning
confidence: 98%
“…Of the various perovskites that are of interest, our group has focused on LSF because it does not react with YSZ at temperatures below 1373 K, 27,28 allowing changes in perovskite microstructure to be examined by varying the calcination temperature of the electrode after infiltration. 3,4,[27][28][29][30][31][32][33] Past work has shown that high calcination temperatures (e.g. 1373 K) dramatically decrease the surface area of the LSF phase and lead to a significant increase in the non-ohmic electrode resistance at open circuit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The two electrolyte materials tested in this study were 10% ScSZ and 8% YSZ. Although ScSZ is significantly more expensive than YSZ, it is mechanically stronger and has a higher ionic conductivity . The cells made with ScSZ had 100‐μm‐thick electrolytes, whereas the YSZ cells had electrolytes that were 160‐μm thick, made by laminating two 80‐μm tapes.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details on the tape-casting procedures can be found in previous publications. 11,12 In some cases, the porous layers were infiltrated with La 0.6 Sr 0. 4 3 .…”
Section: Journal Of the Electrochemical Society 164 (6) F525-f529 (2mentioning
confidence: 99%